Determinação dos períodos críticos de interferência das plantas daninhas sobre o milho (Zea mays L. cv C333) em função da redução de espaçamento da cultura - Melhorança Filho , André Luiz [UNESP] (2005)
The presente work had as objective to study the effects of weeds periods of control on corn plants (Zea mays L.) productivity. The experiment was conducted at Agricultural Science College, UNESP, Botucatu campus, from December 2003 to June 2004. The treatments were constituted of 12 increasing and decreasing familitary periods or weeds control on the cultivation, considered from the corn cultivation emergence, in two spaces (0,90 and 0,45 m). The familiarity periods or evaluated controls were 0-7, 0-14, 0-28, 0-35, 0-42, 0-56, 0-70, 0-98, 0-126. The treatments were arranged in subdivided plots scheme. plants height, stem diameter, total dry matter, leaf area, 100 seeds weight, seeds dampness, corncob weight, total of seeds corncobs and total productivity evaluations were made. The evaluations were made at the end of each control or familiarity period. The obtained data were submitted to statistic analysis through T test. The weeds species tht ocurreed on the experimental area were: Brachiaria plantaginea, Commelina benghalensis, Amaranthus retroflexus, Emilia sonchifolia, Bidens pilosa e Richardia brasiliensis. The results indicated that there was influence of treatments onthe leaf area and final productivity, other characteristics evaluated were not much influenced by studies factors. The final productivity on 0,45 m space was 1,35% higher than on 0,90 m space. Considering all the data together, itþs noted that the weeding made to keep the cultivation without the presence of weeds for at least 70 days, in 0,90 space and 70 days in 0,45 space, after the cultivation emergence, was enough to maintain the minimum levels of infestation of weeds during all the cycle.